Delayed Massive Postoperative Ileal Hemorrhage from an Ileal Dieulafoy Lesion Following Penetrating Abdominal Gunshot Injury: Successful Diagnosis of Obscure Small Bowel Bleeding by Intraoperative Enteroscopy – A Case Report - Min Nay Zar Wyke; Min Htet San; Kyaw Ye Naung Htun; Aung Ko Ko Linn; Kyaw Thu Linn; Thein Maw Myint; Pyae Phyo Kyaw; Oakar Kyaw; Thant Lwyn San; Khin Aung Htun (International Journal of Medical Science and Clinical Research Studies, 2026)
Background: Penetrating abdominal gunshot injuries frequently result in multiple visceral injuries requiring emergency surgical intervention. Delayed postoperative intraluminal hemorrhage after successful repair of traumatic bowel injuries is exceptionally uncommon, particularly when the bleeding originates from the distal ileum and cannot be identified by conventional endoscopic evaluation. Prompt recognition and timely intervention are crucial to prevent catastrophic hemorrhagic shock. Case Presentation: A 28-year-old soldier sustained a penetrating abdominal gunshot injury causing two complete jejunal transections and associated descending colonic injury, requiring emergency laparotomy with segmental jejunal resection, primary anastomoses, and exteriorization of the injured descending colon as a loop colostomy. The initial postoperative recovery was uneventful until postoperative day 10, when he developed sudden massive hemorrhage through the loop colostomy resulting in hemorrhagic shock. Upper gastrointestinal endoscopy and colonoscopy failed to identify the bleeding source. Emergency relaparotomy with intraoperative enteroscopy through a surgically created ileostomy demonstrated a small (approximately 4-5 mm), actively spurting vascular lesion approximately 10 inches proximal to the ileocecal valve. Segmental ileal resection with primary anastomosis achieved definitive hemostasis. Histopathological examination confirmed an ileal Dieulafoy lesion (calibre-persistent submucosal artery) associated with recent hemorrhage, granulation tissue, reactive epithelial mucosal changes, proliferating capillaries, and no evidence of malignancy. The patient recovered completely and subsequently underwent successful colostomy closure after confirmation of distal colonic patency. Conclusion: Delayed postoperative ileal hemorrhage should be considered in patients with persistent gastrointestinal bleeding after abdominal trauma when conventional endoscopy is inconclusive. Intraoperative enteroscopy remains a valuable diagnostic and therapeutic adjunct in selected patients with obscure small bowel bleeding, enabling accurate localization and definitive surgical management.